SHESHENLIK ÓNERINIŃ HÁM SHESHENLER AYTISINIŃ JANRLIQ ÓZGESHELIKLERI - Jollıbaeva, G. (ILIM hám JÁMIYET, 2022)
The article deals with the history of the development of the Chechen profession. At the same time, the oral traditions of the Karakalpak people are revealed through examples of oratory.